Subsidy from State Public Universities and Solidarity Support in Mexico from 2012 to 2021 - Vega, Jose Luis Arcos; Quintero, Marja Johana López; Paredes, Marissa Lopez (Advances in Social Sciences Research Journal, 2024)
The present research is a documentary study that analyzes the trend in annual subsidies granted to the Mexican higher education system in the period from 2012 to 2021, generating an overview of the government’s budget to higher education institutions and its current impact on the system by considering national public spending at both the federal, state and private levels. In addition, it establishes the budget granted in these years to different types of institutions such as State Public Universities (UPES), State Public Universities and Solidarity Support (UPEAS), as well as Technological Universities (UT) and Polytechnic Universities (UP). The institutions have been affected over the years, since the budget granted has not represented an increase in management for the operation of the investment of the universities, as a result, various support programs have had to be sought to cover their recurrent costs which are not sufficient for their teaching operations, research, extension of culture and institutional services and on certain occasions had to resort to intervention with own resources. In conclusion, in 2012 a total of 193,145,10 million current pesos was awarded, However, in 2021 there were only 270,487.30 million pesos corresponding to the support granted nationally to all higher education institutions as a whole, which implies greater expenses for universities throughout the states.